Diminished acquired equivalence yet good discrimination performance in older participants - Robinson, Jasper (Frontiers in Psychology, 2013)
We asked younger and older human participants to perform computer-based configural discriminations that were designed to detect acquired equivalence. Both groups solved the discriminations but only the younger participants demonstrated acquired equivalence. The discriminations involved learning the preferences (‘like’ [+] or ‘dislike’ [-]) for sports (e.g., tennis [t] and hockey [h]) of four fictitious people (e.g., Alice [A], Beth [B], Charlotte [C] & Dorothy [D]). In one experiment, the discrimination had the form: At+, Bt-, Ct+, Dt-, Ah-, Bh+, Ch-, Dh+. Notice that, e.g., Alice and Charlotte are ‘equivalent’ in liking tennis but disliking hockey. Acquired equivalence was assessed in ancillary components of the discrimination (e.g., by looking at the subsequent rate of ‘whole’ versus ‘partial’ reversal learning). Acquired equivalence is anticipated by a network whose hidden units are shared when inputs (e.g., A and C) signal the same outcome (e.g., +) when accompanied by the same input (t). One interpretation of these results is that there are age-related differences in the mechanisms of configural acquired equivalence.